Democracy as Intellectual Taste? Pluralism in Democratic Theory. Issue 3 (2nd October 2018) - Dufek, Pavel
ABSTRACT: The normative and metanormative pluralism that figure among core self-descriptions of democratic theory, which seem incompatible with democratic theorists' practical ambitions, may stem from the internal logic of research traditions in the social sciences and humanities and from the conceptual structure of political theory itself. One way to deal productively with intradisciplinary diversity is to appeal to the idea of a meta-consensus; another is to appeal to the argument from cognitive diversity that fuels recent work on epistemic democracy. For different reasons, both strategies fail, such that a metatheoretical step-aside may be desirable, one that entails modeling democratic theory after the public justification approach.